2020
DOI: 10.1371/journal.pone.0243751
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of community members’ willingness to donate stool for faecal microbiota transplantation

Abstract: Universal stool banks rely on, but face difficulties recruiting, community volunteers to donate stool for faecal microbiota transplantation (FMT) to effectively treat recurrent Clostridioides difficile. This study sought to identify determinants of community members’ willingness to donate stool to guide donor recruitment. 397 Australian residents (52% male, 47% 21–30 years, 63% university educated) completed a survey to gauge willingness to donate stool, bowel habits, information needs, attitudes, barriers, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Blood donation in the year prior was significantly, positively correlated with intention to donate stool 54 . Willingness to donate stool in‐centre was higher amongst those donating blood recently (year prior vs. not) 55 .…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Blood donation in the year prior was significantly, positively correlated with intention to donate stool 54 . Willingness to donate stool in‐centre was higher amongst those donating blood recently (year prior vs. not) 55 .…”
Section: Resultsmentioning
confidence: 94%
“…Blood donation in the year prior was significantly, positively correlated with intention to donate stool. 54 Willingness to donate stool incentre was higher amongst those donating blood recently (year prior vs. not). 55 However, willingness to donate stool at home and deliver it to the centre did not differ between these groups.…”
Section: Willingnessmentioning
confidence: 96%
“…A web-based grey literature search (conducted June 2021) complemented the academic literature search to identify regulations and guidelines for FMT in the case of example countries. Twenty-five papers 17,19,23,25,26,[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] An additional 10 publications, identified through targeted searches (e.g. for updates to regulation and guidance, details on specific health systems initiatives and areas where evidence is contested), were consulted on specific points raised in the literature.…”
Section: Narrative Reviewmentioning
confidence: 99%
“…31,32 Identifying and recruiting donors is a widescale challenge (Int1, 3, 7, expert workshops). 25,33,42,52 FMT programmes and/ or stool banks need to cultivate goodwill amongst individuals to encourage and retain donors, 45 while clearly communicating the voluntary nature of donation to prevent a sense of obligation. 45 Regulations related to donor eligibility can also present a ○ Gastroenterologists and ID specialists (Australia)…”
Section: Recruiting and Retaining Donorsmentioning
confidence: 99%
“…Therefore, the organ recipients express their concerns about the survival of the organ when knowing the donor and ensuring that he/she is young. Forsberg et al also suggested that although the participants do not know the donor, they think about the gender and age of the donor, and this would significantly affect the outcomes (26). In a study, the participants also stated that they were happy to have relationship with the donor's family and would like to know the donor, and that they wanted to know whether the donor was a woman or a man (27).…”
Section: Theme 2: 'Ensure Of Matching His/her Characteristics With Donor's Ones'mentioning
confidence: 99%